Self-leveling high-temperature-resistant wet-process spray coating for blast furnace and preparation method thereof
By optimizing the composition and process flow, a self-leveling high-temperature resistant wet spray coating is provided, which solves the problems of self-leveling, density and thermal shock stability in blast furnace lining construction, and realizes the formation of a highly efficient and stable spray coating, which is suitable for rapid construction and long-life protection of blast furnace lining.
Patent Information
- Application Number
- CN202511009972.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-22
- Publication Date
- 2025-10-17
AI Technical Summary
Existing wet spray coatings have problems such as poor self-leveling, insufficient density, insufficient thermal shock stability and poor construction consistency in blast furnace lining construction, making it difficult to meet the harsh service conditions of blast furnaces, and lacking a unified preparation standard.
Using white corundum aggregate with a particle size of 0.5–3 mm, activated alumina micro powder with a D90 particle size of <10 μm, high alumina cement, silica sol, dehydrated sodium silicate, modified bentonite, and heat-resistant polymer thickener, a self-leveling, dense, and thermally shock-stable spray coating is formed by optimizing the gradation and process flow.
It achieves self-leveling properties and construction stability of the sprayed coating, possesses excellent high-temperature sintering strength and thermal shock stability, significantly extends the service life of the blast furnace lining, reduces the frequency of operation and maintenance, and is suitable for rapid construction under complex working conditions.
Smart Images

Figure SMS_1
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of refractory materials, in particular to a self-leveling high-temperature-resistant wet spraying material for blast furnaces and a preparation method thereof. BACKGROUND
[0002] The blast furnace is a core high-temperature reaction equipment in the modern steel smelting process. The furnace shell, furnace belly, tuyere and other parts are subjected to the scouring of molten iron and slag, high-temperature ablation, chemical corrosion and severe thermal shock stress during operation, and are the most severe service areas in the furnace body. In order to ensure the stable and efficient operation of the blast furnace, the inner lining needs to be maintained and repaired regularly. Among them, spraying repair has become the current mainstream technical means due to its high efficiency and small disturbance.
[0003] The existing spraying materials mainly include dry spraying, semi-dry spraying and wet spraying. Among them, wet spraying gradually becomes the main way for blast furnace lining repair due to its small dust, high density and convenient construction. However, there are still many outstanding problems in the actual application of the existing wet spraying material. On the one hand, the traditional formula generally has the problem of poor self-leveling property. The grading of the ingredients is unreasonable, and the fluidity depends on the water amount adjustment. In the field construction, phenomena such as bleeding, sagging or accumulation often occur, causing unevenness of the sprayed layer surface, thereby causing stress concentration or local peeling and other defects, and reducing the overall service life of the repaired layer. On the other hand, the high-temperature sintering performance of some wet spraying materials is insufficient, and it is difficult to form a dense structure. When serving at a high temperature above 1450℃, loose structure and reduced strength often occur, which cannot meet the severe service conditions of the furnace belly, tuyere and other areas.
[0004] In addition, the existing spraying material is still difficult to balance between thixotropy control, construction stability and thermal shock adaptability. The combined system design lacks systematic optimization. Especially under the condition of multiple thermal shock cycles of the sprayed layer, the material has insufficient crack resistance and is prone to structural failure, resulting in frequent maintenance and premature failure of the furnace lining. At the same time, the existing spraying material preparation process relies on field experience and lacks unified standards, which has poor consistency in pulp preparation and is difficult to meet the industrialization and batch construction needs.
[0005] Therefore, it is urgent to design a self-leveling high-temperature-resistant wet spraying material for blast furnaces and a preparation method thereof to solve the above problems. SUMMARY
[0006] The present application relates to the technical field of refractory materials, in particular to a self-leveling high-temperature-resistant wet spraying material for blast furnaces and a preparation method thereof.
[0007] To achieve the above-mentioned purpose, the present application provides the following technical solutions:
[0008] A self-leveling high-temperature-resistant wet spraying material for blast furnaces, the spraying material comprises the following components by mass fraction:
[0009] White corundum aggregate with particle size of 0.5-3mm: 20-40 parts;
[0010] Active alumina micropowder with D90 particle size <10 μm: 15-25 parts;
[0011] High-alumina cement: 10-20 parts;
[0012] Silica sol with solid content of 30%: 8-15 parts;
[0013] Dehydrated sodium silicate: 2-5 parts;
[0014] Modified bentonite: 1-3 parts;
[0015] Heat-resistant high-molecular thickening agent: 0.3-1.0 parts;
[0016] Defoaming agent: 0.05-0.2 parts;
[0017] Water: 10-25 parts, which is industrial tap water or deionized water, and the amount is adjusted to the slurry flow degree of 30-50 seconds.
[0018] As a preferred technical solution of the present application, the white corundum aggregate has a particle size of 2-3mm, and the active alumina micropowder is treated by ball milling to improve the reaction activity and porcelain strength.
[0019] As a preferred technical solution of the present application, the thickening agent is hydroxypropyl methylcellulose ether, sodium polyacrylate or CMC-Na, and the defoaming agent is polyether-modified siloxane.
[0020] As a preferred technical solution of the present application, the sprayed material has the following performance parameters after preparation: the self-leveling flow degree of the slurry is 35±5 seconds, which is measured by a self-leveling instrument according to the JC / T 2461 standard; the compressive strength after 24 hours of normal temperature curing is not less than 40 MPa, and the compressive strength after sintering treatment at 1450℃ for 3 hours is not less than 70 MPa; no cracks are generated after 25 cycles of high-temperature heating at 1100℃ and water cooling, and excellent thermal shock stability is achieved, which is tested according to the YB / T 2206 standard; the bulk density after 24 hours of drying at 110℃ is not less than 2.4 g / cm 3 , which meets the GB / T 2997 test standard.
[0021] The present application also provides a preparation method of a self-leveling high-temperature-resistant wet-sprayed material for blast furnaces, which comprises the following steps, and the mass parts of each component are controlled within the ranges as claimed in claim 1:
[0022] (1) Raw material pretreatment: 20-40 parts of white corundum aggregate are screened, impurities are removed, and then dried for standby use;
[0023] (2) Dry powder premix: take 15-25 parts of active alumina powder, 10-20 parts of high alumina cement and 1-3 parts of modified bentonite, put them into a dry mixer and mix for 3-5 minutes to obtain a dry powder mixture;
[0024] (3) Liquid phase preparation: take 8-15 parts of silica sol and 2-5 parts of dehydrated sodium silicate, mix them uniformly, then add 0.3-1.0 parts of heat-resistant thickening agent and 0.05-0.2 parts of defoaming agent, and stir them uniformly to form a liquid phase component;
[0025] (4) Slurry preparation and stirring: put the white corundum aggregate obtained in step (1), the dry mixture of step (2) and the liquid phase component of step (3) into a high-speed forced stirrer in sequence, and gradually add 10-25 parts of water during the stirring process to control the slurry flow degree to 35±5 seconds;
[0026] (5) Aging and spraying: after the slurry is placed for 5-10 minutes, it is uniformly sprayed on the lining surface of the blast furnace by using a wet spraying device, and the construction thickness is controlled to be 10-50 mm.
[0027] As a preferred technical solution of the present application, the actual amount of water is adjusted according to the environmental temperature and humidity to ensure that the sprayed slurry maintains no bleeding, no sagging and self-leveling performance for not less than 20 minutes.
[0028] As a preferred technical solution of the present application, the step 4 stirring process uses a high-speed forced vertical stirrer, the stirring speed is 60-100 rpm, and the duration is controlled to be 3-5 minutes.
[0029] As a preferred technical solution of the present application, the slurry should be used up within 60 minutes after preparation, and the flowability and thixotropic properties will be lost if the time exceeds.
[0030] As a preferred technical solution of the present application, after the spraying is completed, it should be naturally cured in an environment of 15-30℃ for more than 24 hours to avoid direct sunlight and strong wind cracking, and the sprayed material is suitable for lining repair or spraying protection in high-temperature areas of the blast furnace hearth, bosh, tuyere and furnace wall, has excellent thermal shock stability, sintering strength, slag erosion resistance and self-leveling construction performance, and is suitable for rapid construction and efficient maintenance requirements under complex working conditions.
[0031] Compared with the prior art, the present application has the following beneficial effects:
[0032] The application provides a self-leveling high-temperature-resistant wet spraying material for blast furnaces, which realizes good flowability control and construction stability by optimizing the particle gradation of white corundum aggregate and active alumina micropowder, combining a high-aluminum cement and silica sol composite bonding system, and being supplemented with modified bentonite, heat-resistant thickening agent and high-temperature stable defoaming agent. The formula design makes the slurry have excellent self-leveling performance and thixotropy retention, can automatically spread and level during the wet spraying process, avoids phenomena such as bleeding, piling and sagging, and significantly improves the surface quality and forming compactness of the sprayed layer.
[0033] The multi-component synergistic bonding system adopted in the application can form a continuous and stable ceramic sintering structure under high-temperature conditions, so that the sprayed layer has high post-sintering compressive strength and thermal shock stability. The material still maintains excellent structural integrity after sintering at 1450 DEG C, and can stably withstand more than 25 times of cold and hot impact without cracking in the 1100 DEG C water cooling thermal shock cycle test, fully meeting the use requirements of the high-temperature impact strong area such as the blast furnace tuyere, bosh and hearth, significantly prolonging the service life of the furnace lining and reducing the operation and maintenance frequency.
[0034] In addition, the application establishes a standardized and popularized preparation process, from raw material screening, dry mixing pretreatment, liquid phase preparation to stirring aging and spraying operation, which has clear ratio and process parameter control, is convenient for large-scale production and rapid construction on site, ensures the consistency of the spraying material performance and the reliability of the engineering application, has good industrial adaptability and popularization prospect. DETAILED DESCRIPTION
[0035] The technical solutions of the application will be described clearly and completely in combination with several embodiments. Obviously, the following described embodiments are only a part of the embodiments of the application, rather than all the embodiments. Based on the embodiments in the application, all other embodiments obtained by those skilled in the art without creative labor are within the protection scope of the application. In order to make the technical solutions and implementation modes of the application clearer and more understandable, the following introduces specific examples preferred for implementing the technical solutions of the application.
[0036] The application provides a self-leveling high-temperature-resistant wet spraying material suitable for the blast furnace hearth, bosh and tuyere area and a preparation method thereof. The spraying material formula design is reasonable, the construction is convenient, and the spraying material has good self-leveling performance, high-temperature resistance and thermal shock stability. The application will be further described in detail in combination with the embodiments.
[0037] Example 1: Formulation composition (unit: mass parts): white corundum aggregate (particle size 2-3 mm): 30; active alumina powder (D90<10 μm, ball milling treatment): 20; high-alumina cement: 15; silica sol with solid content of 30%: 12; dehydrated sodium silicate: 3; modified bentonite: 2; hydroxypropyl methylcellulose ether (HPMC): 0.5; polyether-modified siloxane antifoaming agent: 0.1; industrial tap water: 18 (adjusted to a fluidity of 35 seconds);
[0038] Preparation method: (1) The white corundum aggregate was sieved to a particle size of 2-3 mm and dried at 110°C for 2 hours for standby use;
[0039] (2) The active alumina powder, high-alumina cement and modified bentonite were put into a dry mixing blender and dry mixed for 4 minutes to obtain a dry powder;
[0040] (3) The silica sol and dehydrated sodium silicate were mixed, and then the HPMC and antifoaming agent were added in sequence, and stirred to form a liquid component;
[0041] (4) The aggregate, dry powder and liquid component were sequentially added into a high-speed vertical forced stirrer, and 18 parts of industrial tap water were slowly added during stirring, and the stirring speed was controlled at 80 rpm, and the stirring time was 4 minutes;
[0042] (5) After completion of stirring, the slurry was left to stand for 7 minutes for aging, and then used after the slurry was fully matured;
[0043] (6) The test block for blast furnace was sprayed using a wet spraying equipment, and the spraying thickness was 25 mm, and the construction surface was smooth and flat;
[0044] (7) After completion of construction, the natural curing was performed for 24 hours, and the environmental temperature was controlled at 20-25°C, and strong wind and sunlight were avoided.
[0045] Performance test:
[0046] Fluidity: 35 seconds (JC / T 2461);
[0047] Cold compressive strength (24h): 42.3 MPa;
[0048] Baked compressive strength (1450°C x 3h): 76.4 MPa;
[0049] Thermal shock stability (1100°C water cooling): 26 times without cracking (YB / T 2206);
[0050] Dried bulk density (110°C x 24h): 2.46 g / cm 3 .
[0051] Example 2: Formula composition: white corundum aggregate (particle size 2-3 mm): 35; active alumina powder: 17; high-alumina cement: 18; silica sol with solid content of 30%: 10; dehydrated sodium silicate: 4; modified bentonite: 1.5; polyacrylic acid sodium thickener: 0.8; polyether defoaming agent: 0.1; industrial tap water: 20;
[0052] Preparation method:
[0053] (1) The white corundum aggregate is sieved and dried;
[0054] (2) The active alumina powder, high-alumina cement, and modified bentonite are dry mixed for 3 minutes;
[0055] (3) The silica sol and dehydrated sodium silicate are premixed, and then the thickener and defoaming agent are added and stirred to form a liquid phase;
[0056] (4) The aggregate, dry mixed material, and liquid phase are sequentially added to a stirrer, and 20 parts of water are gradually added at a stirring rate of 90 rpm for 4 minutes to prepare a slurry with a fluidity of 38 seconds;
[0057] (5) After aging for 6 minutes, spraying is performed with a thickness of about 40 mm, and curing is performed for 24 hours.
[0058] Performance test results:
[0059] Fluidity: 38 seconds;
[0060] Room temperature compressive strength: 45.1 MPa;
[0061] Baked compressive strength: 72.8 MPa;
[0062] Thermal shock stability: 25 times;
[0063] Dried bulk density: 2.42 g / cm 3 .
[0064] Example 3:
[0065] Formula composition: white corundum aggregate: 25; active alumina powder: 25; high-alumina cement: 10; silica sol: 14; dehydrated sodium silicate: 2; modified bentonite: 3; CMC-Na thickener: 0.4; defoaming agent: 0.05; deionized water: 21;
[0066] Preparation method:
[0067] (1) The white corundum aggregate is sieved and reserved;
[0068] (2) The active alumina powder, cement, and bentonite are dry mixed for 5 minutes;
[0069] (3) The liquid additives are sequentially added to the liquid phase and stirred uniformly;
[0070] (4) Add water to control the fluidity to 34 seconds, stir evenly, and stand for 8 minutes;
[0071] (5) Spray to the simulated furnace lining of the tuyere with a thickness of 20 mm, and maintain for 24 hours.
[0072] Performance:
[0073] Fluidity: 34 seconds;
[0074] Cold compressive strength: 43.5 MPa;
[0075] Baked strength: 75.5 MPa;
[0076] Thermal shock times: 27 times;
[0077] Bulk density: 2.48 g / cm 3 .
[0078] Comparative Example 1 (without silica sol): Formula: white corundum aggregate: 30; active alumina powder: 20; high alumina cement: 15; dehydrated sodium silicate: 3; modified bentonite: 2; HPMC: 0.5; defoaming agent: 0.1; water: 18;
[0079] Process: the same as above;
[0080] Performance results: fluidity: 36 seconds;
[0081] Cold compressive strength: 28.7 MPa;
[0082] Baked compressive strength: 48.3 MPa;
[0083] Thermal shock stability: 14 times;
[0084] Dried bulk density: 2.30 g / cm 3 .
[0085] Data summary table:
[0086]
[0087] In summary, through the detailed verification of Examples 1 to 3, it can be seen that the self-leveling high-temperature-resistant wet spray material for blast furnaces provided by the application takes into account sintering strength, self-leveling performance and thermal shock stability in the formula design, and combined with a reasonable construction preparation process, a dense, flat and durable sprayed protective layer can be formed in a high-temperature strong erosion environment, significantly improving the service life and maintenance efficiency of the furnace lining. Compared with the comparative examples, the formula with the addition of silica sol and a composite thickening system has significant advantages in various performance indicators, fully embodying the technical innovation and practical value of the application in structural compatibility, performance balance and construction adaptability, and is suitable for popularization and application in blast furnace lining repair and high-temperature industrial fields.
[0088] Although the present application has been described in detail with reference to the foregoing embodiments, the technical solutions recorded in the foregoing embodiments can be modified by those skilled in the art, or some of the technical features thereof can be replaced by equivalent features, and any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.
Claims
1. A self-leveling high-temperature resistant wet spray coating for blast furnaces, characterized in that: The spray coating comprises the following components in parts by mass: White corundum aggregate with particle size of 0.5-3mm: 20-40 parts; Activated alumina powder with a D90 particle size of less than 10 μm: 15-25 parts; High alumina cement: 10-20 parts; Silica sol with 30% solid content: 8-15 parts; Dehydrated sodium silicate: 2-5 parts; Modified bentonite: 1-3 parts; Heat-resistant polymer thickener: 0.3-1.0 part; Defoaming agent: 0.05-0.2 parts; Water: 10-25 parts, the water is industrial tap water or deionized water, and the amount added is adjusted to the slurry fluidity of 30-50 seconds.
2. The self-leveling high temperature resistant wet spray coating for blast furnace according to claim 1, characterized in that: The white corundum aggregate has a particle size of 2 to 3 mm, and the activated alumina powder is ball-milled to enhance the reaction activity and the porcelain strength.
3. The self-leveling high temperature resistant wet spray coating for blast furnace according to claim 1, characterized in that: The thickener is hydroxypropyl methylcellulose ether, sodium polyacrylate or CMC-Na; the defoaming agent is polyether-modified silicone.
4. The self-leveling high temperature resistant wet spray coating for blast furnace according to claim 1, characterized in that: The spray coating has the following performance parameters after formulation: the self-leveling fluidity of the slurry is 35±5 seconds, as measured using a self-leveling instrument in accordance with JC / T 2461 standard; the compressive strength after 24 hours of room temperature curing is not less than 40 MPa, and the compressive strength after sintering at 1450°C for 3 hours is not less than 70 MPa; the spray coating has no cracks after 25 cycles of water cooling after high-temperature heating at 1100°C, and has excellent thermal shock stability, as tested in accordance with YB / T 2206 standard; Its bulk density after drying at 110℃ for 24 hours is not less than 2.4g / cm 3 , in line with GB / T2997 test standards.
5. A method for preparing the self-leveling high-temperature resistant wet spray coating for blast furnaces according to any one of claims 1 to 4, characterized in that: The method comprises the following steps, wherein the mass parts of each component used are controlled within the range described in claim 1: (1) Raw material pretreatment: Weigh 20-40 parts of white corundum aggregate, sieve and remove impurities, and then dry for later use; (2) Dry powder premixing: Weigh 15-25 parts of activated alumina powder, 10-20 parts of high alumina cement, and 1-3 parts of modified bentonite, put them into a dry mixer and mix for 3-5 minutes to prepare a dry powder mixture; (3) Liquid phase preparation: Weigh 8-15 parts of silica sol and 2-5 parts of dehydrated sodium silicate, mix well, add 0.3-1.0 parts of heat-resistant thickener and 0.05-0.2 parts of defoamer, and stir well to form a liquid phase component; (4) slurry preparation and stirring: the white corundum aggregate obtained in step (1), the dry blended material obtained in step (2), and the liquid phase component in step (3) are sequentially added into a high-speed forced mixer, and 10 to 25 parts of water are gradually added during the stirring process, and the slurry fluidity is controlled to 35 ± 5 seconds; (5) Aging and spraying: After the slurry is left to stand for 5 to 10 minutes, it is evenly sprayed on the lining surface of the blast furnace using wet spraying equipment, and the construction thickness is controlled at 10 to 50 mm.
6. The method according to claim 5, characterized in that The actual amount of water added is adjusted according to the ambient temperature and humidity to ensure that the spray slurry remains free of water exudation, sagging, and self-leveling properties for at least 20 minutes.
7. The method according to claim 5, characterized in that The stirring process in step 4 uses a high-speed forced vertical mixer with a stirring speed of 60-100 rpm and a duration controlled at 3-5 minutes.
8. The method according to claim 5, characterized in that The slurry should be used within 60 minutes after preparation, otherwise it will lose its fluidity and thixotropic properties.
9. The method according to claim 5, characterized in that After spraying, it should be naturally cured in an environment of 15-30℃ for more than 24 hours to avoid direct sunlight and strong wind.